The prevalence of non-syndromic orofacial clefts and associated congenital heart diseases of a tertiary hospital in Riyadh, Saudi Arabia - Ziyad AlHammad; Ihab Suliman; Sami Alotaibi; Hourya Alnofaie; Waad Alsaadi; Sarah Alhusseini; Ghadah Aldakheel; Noura Alsubaie (Elsevier, 2021)
Background: Orofacial clefts are considered one of the most common birth defects and are frequently associated with other malformations. Congenital heart disease is one of the most prevalent congenital malformation. Objective: To investigate the prevalence of congenital heart diseases associated with non-syndromic orofacial clefts in the Saudi population. Methods: Electronic files of non-syndromic orofacial cleft patients who visited the Oral and Maxillofacial Surgery Department in King Abdulaziz Medical City of Riyadh, Saudi Arabia from January 2015 to December 2018 were retrospectively reviewed. Data were recorded in an excel sheet and analyzed using SPSS via frequency tests. Results: In the cleft children identified, the prevalence of non-syndromic orofacial clefts was (77%). Orofacial clefts showed a male predominance (62%). The most common orofacial phenotype was unilateral cleft lip and palate (34%). The prevalence of associated congenital malformations with orofacial clefts was (41%). The most prevalent congenital malformation was congenital heart disease (35%), mainly found in unilateral cleft lip and palate patients (33%). The prevalence of associated congenital heart disease with orofacial clefts was (19%). The most frequent type of congenital heart disease was atrial septal defect (37%). Conclusion: This study highlights the recognition of the associated congenital heart disease with non-syndromic orofacial cleft patients. Global screening protocols designed for newborns with non-syndromic orofacial cleft are needed to eliminate late diagnosis of critical congenital heart diseases which might present operative risks of anesthesia and/or surgical procedures.